Chronic Energy Deficiency in Pregnant Women: A Case Study in the Sawa Community Health Center Area, North Konawe Regency - La Ode Liaumin Azim; Pitrah Asfian; La Ode Ahmad Saktiansyah; Akifah (Sekolah Tinggi Ilmu Kesehatan Garuda Putih, 2025)
Chronic energy deficiency (CED) is one of the nutritional problems commonly found in pregnant women in Indonesia, which can affect the health of the mother and fetus. CED in pregnant women is associated with various factors, including the mother's age and parity. At the Sawa Community Health Center in North Konawe Regency, the prevalence of CED in pregnant women is still quite high. This study aims to analyze the relationship between maternal age and parity with the incidence of CEM in pregnant women at the Sawa Community Health Center in North Konawe Regency. This study used a quantitative research design with a cross-sectional approach. This study was conducted in the working area of the Abuki Community Health Center, from July 4, 2025, to August 2, 2025. The population in this study consisted of all 222 pregnant women in the working area of the Abuki Community Health Center from January to April 2025, with a sample size of 158 respondents. The sampling technique used in this study was accidental sampling. Data analysis was performed using the Chi-Square statistical test with a significance level of p-value 0.05. The results of the chi-square statistical test on the variable of maternal age obtained a p-value of 0.033 and parity obtained a p-value of 0.000. There is a relationship between maternal age and the occurrence of chronic energy deficiency in pregnant women, and there is no relationship between parity and the occurrence of chronic energy deficiency in pregnant women. Therefore, more intensive prevention and intervention efforts need to be focused on this group of pregnant women to prevent CED and improve maternal and fetal health.